Evaluation of the Easy Albumin–Bilirubin Score as a Prognostic Tool for Mortality in Adult Trauma Patients in the Intensive Care Unit: A Retrospective Study - Pao-Jen Kuo; Cheng-Shyuan Rau; Ching-Hua Tsai; Sheng-En Chou; Wei-Ti Su; Shiun-Yuan Hsu; Ching-Hua Hsieh (Diagnostics, 2023)
The easy albumin–bilirubin (EZ–ALBI) score is derived using the following equation: total bilirubin (mg/dL) − 9 × albumin (g/dL). This study aimed to determine whether the EZ–ALBI score predicted mortality risk in adult trauma patients in an intensive care unit (ICU). Data from a hospital’s trauma database were retrospectively evaluated for 1083 adult trauma ICU patients (139 deaths and 944 survivors) between 1 January 2016 and 31 December 2021. Patients were classified based on the ideal EZ–ALBI cut-off of −26.5, which was determined via receiver operating characteristic curve analysis. The deceased patients’ EZ–ALBI scores were higher than those of the surviving patients (−26.8 ± 6.5 vs. −30.3 ± 5.9, p = 0.001). Multivariate logistic analysis revealed that, in addition to age, the presence of end-stage renal disease, Glasgow Coma Scale scores, and injury severity scores, the EZ–ALBI score is an independent risk factor for mortality (odds ratio (OR), 1.10; 95% confidence interval (CI): 1.06–1.14; p = 0.001)). Compared with patients with EZ–ALBI scores < −26.5, those with scores ≥ −26.5 had a 2.1-fold higher adjusted mortality rate (adjusted OR, 2.14; 95% CI: 1.43–3.19, p = 0.001). In conclusion, the EZ–ALBI score is a substantial and independent predictor of mortality and can be screened to stratify mortality risk in adult trauma ICU patients.